2022
DOI: 10.3390/diseases10040099
|View full text |Cite
|
Sign up to set email alerts
|

Association of Alleles of Human Leukocyte Antigen Class II Genes and Severity of COVID-19 in Patients of the ‘Red Zone’ of the Endocrinology Research Center, Moscow, Russia

Abstract: The aim of this study was to assess the correlations of clinical features of patients with moderate and severe courses of COVID-19, comorbidity (endocrine, autoimmune, cardiovascular, oncological, and pulmonary diseases), and alleles of the HLA class II system genes. One hundred COVID-19 patients hospitalized in the Endocrinology Research Centre, Moscow, Russia, were analyzed for age, gender, smoking, comorbidity, and invasive mechanical ventilation. Computer tomography was used to assess the severity of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Applying the computational BA prediction tool, 37 of those epitopes exposed a considerable BA to either HLA-DQ2 or HLA-DQ8 alleles (20 associated with NSP12, 13 with NSP13, 3 with the spike glycoprotein, and 1 with NSP3). Higher sequence similarity and a more effective affinity to specific HLAs were associated with a higher antibody response, thus conferring more efficient protection against a virus [8,23,[26][27][28][29][30][31][32][33][34][35][36]104,108]. A similar explanation can explain the fact that CD patients are relatively protected against COVID-19.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Applying the computational BA prediction tool, 37 of those epitopes exposed a considerable BA to either HLA-DQ2 or HLA-DQ8 alleles (20 associated with NSP12, 13 with NSP13, 3 with the spike glycoprotein, and 1 with NSP3). Higher sequence similarity and a more effective affinity to specific HLAs were associated with a higher antibody response, thus conferring more efficient protection against a virus [8,23,[26][27][28][29][30][31][32][33][34][35][36]104,108]. A similar explanation can explain the fact that CD patients are relatively protected against COVID-19.…”
Section: Discussionmentioning
confidence: 87%
“…The protective role of HLAs against bacteria [112], parasites [113], and even viruses is well reported. Their role in fighting viruses like HIV [114], HCV [115], HBV [116], and SARS [8,[26][27][28][29][30][31][32][33][34][35][36][117][118][119] have been documented. Interestingly, the protective role of the CD-associated HLA II suggested by Greco N et al [23] represents a refreshing new idea that can help in our understanding of the celiac-COVID-19-HLA axis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Novelli et al. observed that DRB1*15:01, -DQB1*06:02, and -B*27:07 alleles predispose patients to a worse course of COVID-19 disease ( 110 , 111 ). Thus, this excessive response associated with this allele may be more closely related to an increased risk of autoimmunity ( 112 ).…”
Section: Similarity In Genetic Predispositionmentioning
confidence: 99%
“…However, these figures almost certainly constitute an underestimation of the true number of cases and deaths. The pandemic has put health systems under pressure in both developing and high-income countries [ 2 , 3 ]. With this in mind, national health systems are expected to be able to answer to the following questions: how do we manage the current epidemic?…”
mentioning
confidence: 99%